Redevelopment of Female Student Dormitories of Universitas Sumatera Utara with Tropical Architecture Approach - Harisdani, Devin Defriza; Matondang, Maylinda Yunizar (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
The University of North Sumatera (USU) experiences an increase in the number of students each year, increasing the need for adequate female dormitories. Currently, USU's female dormitories are not enough to accommodate all students, forcing many of them to live off-campus, which is less conducive. This research aims to design the development of a girls' dormitory with a tropical architecture approach. This was chosen to create an environmentally friendly, energy-efficient, and comfortable building for residents. The development will be done with a focus on increasing the number of rooms. The design will consider the climate, local culture, and the needs of female students. This development is expected to provide adequate accommodation solutions and a sustainable environment.